1993
DOI: 10.1071/mf9930811
|View full text |Cite
|
Sign up to set email alerts
|

Movement of tagged juvenile tailor (Pomatomus saltatrix) in Moreton Bay, Queensland

Abstract: Large quantities of tailor, Pomatomus saltatrix, are caught by recreational and commercial fishers in coastal waters off New South Wales and Queensland. Juvenile tailor were subject to increasing fishing mortality in Moreton Bay (Queensland) in the mid 1980s. A tagging programme, involving State Government fisheries biologists and amateur fishing clubs, was established in 1986 to examine the movement, growth rate and fisheries exploitation of juvenile tailor (<270 mm fork length) in Moreton Bay. Of 217… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 0 publications
2
19
1
Order By: Relevance
“…We also gather some information from a few detailed surveys on this fish species conducted in south Brazilian coast Krug, 1992, 1996;Muelbert and Sinque, 1996;Lucena et al, 2000), thousands of kilometers south of Búzios Island or in eastern Australian coast (but not exactly in Moreton Bay region) (Zeller et al, 1996). We found only one published survey about this fish species in Moreton Bay (Morton et al, 1993), addressing migratory movements of juveniles. The species names of fishes and other animals mentioned by fishers were gathered from fish species collected in Brazil (Begossi and Figueiredo, 1995;Silvano, 2001) and from literature in Australia (Grant, 1985;Kuiter, 1997;Quandamooka Land and Sea Management Agency, unpublished report, 1999).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We also gather some information from a few detailed surveys on this fish species conducted in south Brazilian coast Krug, 1992, 1996;Muelbert and Sinque, 1996;Lucena et al, 2000), thousands of kilometers south of Búzios Island or in eastern Australian coast (but not exactly in Moreton Bay region) (Zeller et al, 1996). We found only one published survey about this fish species in Moreton Bay (Morton et al, 1993), addressing migratory movements of juveniles. The species names of fishes and other animals mentioned by fishers were gathered from fish species collected in Brazil (Begossi and Figueiredo, 1995;Silvano, 2001) and from literature in Australia (Grant, 1985;Kuiter, 1997;Quandamooka Land and Sea Management Agency, unpublished report, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…North Stradbroke is a sand island with a great extension of oceanic beach. Along the east coast of Australia, schools of P. saltatrix occur in surf zones of oceanic beaches (Grant, 1985;Kailola et al, 1993;Morton et al, 1993), which are suitable habitats for fishing with haul nets (seine nets). For the Brazilian Búzios Island, fishermen did not mention sand beaches or estuaries as P. saltatrix habitats, as there are only rocky shores, which are not suitable for fishing with haul nets.…”
Section: Ethnoecology Of P Saltatrix In Brazil and Australiamentioning
confidence: 98%
“…For example, Russell & Garrett (1988) found that only 2.5% of all tagged barramundi Lates calcarifer were caught away from the tidal creeks in which they were tagged. Limited movement was also found for tailor/bluefish Pomatomus saltatrix that were tagged in Morton Bay estuary (Queensland, Australia), with no fish moving outside of Morton Bay, and all fish being recaptured within 85 km of tagging, a relatively small distance considering the wide range of the species (Morton et al 1993). Results suggesting limited movement may be due to the fact that recapture efforts are usually concentrated near the site(s) where tagging occurred.…”
Section: Artificial Tagsmentioning
confidence: 88%
“…Evidence from tagging studies indicates that age-0 bluefish can remain resident in localized estuary habitats (i.e. 0 to 5 km) for periods of weeks to months (Morton et al 1993, Able et al 2003, whereas juveniles in coastal ocean habitats display higher mobility (i.e. 10+ km) and reduced site fidelity (Morton et al 1993, Able et al 2003.…”
Section: Inner Continental Shelf Vs Estuarine Foraging Conditionsmentioning
confidence: 99%
“…0 to 5 km) for periods of weeks to months (Morton et al 1993, Able et al 2003, whereas juveniles in coastal ocean habitats display higher mobility (i.e. 10+ km) and reduced site fidelity (Morton et al 1993, Able et al 2003. In creased spatial mixing and, presumably, spatial foraging of shelf individuals would lead to a more homogenous isotopic signature among shelf bluefish.…”
Section: Inner Continental Shelf Vs Estuarine Foraging Conditionsmentioning
confidence: 99%